FAILURE OF ELECTRIC MOTOR-DRIVEN PUMP BOEING SYSTEM 737-800 - Anggun Nurul Hidayah (Institut Teknologi Dirgantara Adisutjipto, 2021)
This study aims to determine the results of the analysis of the causes a failure that occurred in the Electric Motor-Driven Pump system on an aircraft. Boeing 737-800. The data used is in the form of a Pilot Report from the Batik airline.Water in the period 2013 to 2020.The method used in this research is Failure Mode and Effect Criticality Analysis (FMECA). FMECA is a method used to analyze the causes of damage to a system / component,along with the effects if there is damage to the system / component. The first step in this research is to find case data happened to the hydraulic system (ATA 29) on the airline Batik Air, then perform data processing. From the results of the analysis, the results of the RPN value on Electric Motor-Driven.The highest pump is because EMDP cannot supply pressure to the system. Based on the RPN calculation, the RPN value was obtained at 12. This value obtained from the matrix in the safety standard manual from Batik Air.